The role of communication and collaboration influencing teachers’ professional motivation - Gabnytė, Giedrė; Strakšienė, Diana (Social Welfare: Interdisciplinary Approach, 2019)
The article addresses one of the most important factors of teachers’ professional motivation, communication and collaboration, in the context of the education process understood as a system of interaction of all members of the education process. The main idea of the empirical research introduced in this article is to reveal and generalise aspects of communication and collaboration in Lithuanian non-formal music education (in music schools), while thoroughly analysing the aspect of relationships between an educator and students, an educator and parents, an educator and an educator, an educator and a school principal. The research shows that the relation between teacher and student in the process of music education is clearly characteristic of manifestations of authoritarianism in education. When evaluating manifestation of the relationship between a teacher and parents, a teachers’ positive attitudes towards mutual collaboration have been found out; nevertheless, interrelations among teachers in school are based on competitiveness. The relationship between a school principal and teachers is ambiguously evaluated by teachers themselves: in some cases, it is characterised as positive, whereas in other cases it is perceived as negative; nevertheless, in all cases it is considered as making an impact on the entire education process.
Keywords: teachers’ professional motivation; communication and collaboration; music school